Branched-chain amino acid supplementation increases the lactate threshold during an incremental exercise test in trained individuals - Matsumoto, K.(Otsuka Pharmaceutical Co. Ltd., Saga (Japan)); Koba, T; Hamada, K; Tsujimoto, H; Mitsuzono, R (Journal of Nutritional Science and Vitaminology, 2009)
The effects of branched-chain amino acid (BCAA) supplementation on the lactate threshold (LT) were investigated as an index of endurance exercise capacity. Eight trained male subjects (21+-2 y) participated in a double-blind crossover placebo-controlled study. The subjects were randomly assigned to two groups and were provided either a BCAA drink (0.4% BCAA, 4% carbohydrate; 1,500 mL/d) or an iso-caloric placebo drink for 6 d. On the 7th day, the subjects performed an incremental loading exercise test with a cycle ergometer until exhaustion in order to measure the LT. The test drink (500 mL) was ingested 15-min before the test. Oxygen consumption (VO2) and the respiratory exchange ratio (RER) during the exercise test were measured with the breath-by-breath method. Blood samples were taken before and during the exercise test to measure the blood lactate and plasma BCAA concentrations. The same exercise test was performed again 1 wk later. BCAA supplementation increased the plasma BCAA concentration during the exercise test, while plasma BCAA concentration decreased in the placebo trial. The RER during the exercise test in the BCAA trial was lower than that in the placebo trial (p0.05). The VO2 and workload levels at LT point in the BCAA trial were higher than those in the placebo trial (VO2: 29.8+-6.8 vs. 26.4+-5.4mL/kg/min; workload: 175+-42 vs. 165+-38 W, p0.05, respectively). The VO2max in the BCAA trial was higher than that in the placebo trial (47.1+-5.7 vs. 45.2+-5.0 mL/kg/min, p0.05). These results suggest that BCAA supplementation may be effective to increase the endurance exercise capacity.